Closing the gate : race, politics, and the Chinese Exclusion Act - Gyory, Andrew (Immigration law & policy in the U.S., 1998)
The Chinese Exclusion Act of 1882, which barred practically all Chinese from American shores for ten years, was the first federal law that banned a group of immigrants solely on the basis of race or nationality. By changing America's traditional policy of open immigration, this landmark legislation set a precedent for future restrictions against Asian immigrants in the early 1900s and against Europeans in the 1920s. Tracing the origins of the Chinese Exclusion Act, Andrew Gyory presents a bold new interpretation of American politics during Reconstruction and the.